Politicas ambientales para el control de la contaminación difusa en el regadío - Martínez Martínez, Yolanda; Albiac Murillo, José (Geographicalia, 2016)
Non-point source pollution control is an important question for the implementation of the Water Framework Directive. This article analyzes several policy measures to control nitrate pollution in the Flumen-Monegros irrigation district (Huesca). Policy options are evaluated considering the cost-efficiency of measures, by comparing the effects of each rneasure on farmers net income and pollution abatement.